Everyday culture of the Nogais in the second half of the 19th–early 20th centuries: comparative analysis - D. S. Kidirniyazov; B. B. Abdulvakhabova (Nomadic Civilization: Historical Research, 2024)
After the collapse of the Golden Horde, the Nogai Horde as a new Nogai state formation in the south of Russia arose. A small group of the Nogais, settled on the territory of modern Chechnya, created a national minority, but today they occupy a worthy place in the ethnocultural environment of the region. The study of cultural and everyday processes of the peoples living in the Chechen Republic, including the Nogais, is relevant. Simultaneously living in this territory, all national groups are in contact with each other, which leads to the dynamic development of ethnic processes, the interaction of cultural and economic activities, material culture, and ethnocultural relationships in such a densely populated area as the North Caucasus. The relevance of the study lies not only in the scientific and educational aspect, but also in the description of the interethnic, ethnocultural relationships of the peoples of Russia, both in the past and in the present, since these relationships do not lose their significance at the present time. For a more contrasting illumination of the current situation of cultural and everyday processes of the Nogai people in the presented study, the authors will try to provide a historical excursion into the past of this nomadic people living on the territory of the Chechen Republic (subject of the Russian Federation).